Population Pharmacokinetics and Exposure–Response (Efficacy and Safety/Tolerability) of Empagliflozin in Patients with Type 2 Diabetes. Issue 3 (September 2016) - Baron, Kyle; Macha, Sreeraj; Broedl, Uli; Nock, Valerie; Retlich, Silke; Riggs, Matthew
Abstract Introduction The aim of the analysis was to characterize the population pharmacokinetics (PKs) and exposure–response (E–R) for efficacy (fasting plasma glucose, glycated hemoglobin) and safety/tolerability [hypoglycemia, genital infections, urinary tract infection (UTI), and volume depletion] of the sodium glucose cotransporter 2 inhibitor, empagliflozin, in patients with type 2 diabetes mellitus. This study extends the findings of previous analyses which described the PK and pharmacodynamics (PD) using early clinical studies of up to 12 weeks in duration. Methods Population pharmacokinetic and E–R models were developed based on two Phase I, four Phase II, and four Phase III studies. Results Variability in empagliflozin exposure was primarily affected by estimated glomerular filtration rate (eGFR) (less than twofold increase in exposure in patients with severe renal impairment). Consistent with its mode of action, the efficacy of empagliflozin was increased with elevated baseline plasma glucose levels and attenuated with decreasing renal function, but was still maintained to nearly half the maximal effect with eGFR as low as 30 mL/min/1.73 m2 . All other investigated covariates, including sex, body mass index, race, and age did not alter the PK or efficacy of empagliflozin to a clinically relevant extent. Compared with placebo, empagliflozin administration was associated with an exposure-independent increase in the incidence of genital infections and no significant change in the risk of UTI, hypoglycemia, or volume depletion. Conclusion Based on the results from the PK and E–R analysis, no dose adjustment is required for empagliflozin in the patient population for which the drug is approved. Funding Boehringer Ingelheim.